2007
DOI: 10.1175/jtech1986.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Horizontal Pressure Gradient Force Using Global Positioning System on board an Instrumented Aircraft

Abstract: The horizontal pressure gradient force is the single most important dynamical term in the equation of motion that governs the forcing of the atmosphere. It is well known that the slope of an isobaric surface is a measure of the horizontal pressure gradient force. Measurement of this force over mesoscale distances using an airborne platform has been attempted for over two decades in order to understand the dynamics of various wind systems. The most common technique has been to use a radar altimeter to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…As the autopilot is trying to maintain a constant pressure altitude, the variations in P C along a leg, especially for longer disturbances, come primarily from altitude (z) variations. This kind of correction has been made for several decades over water using a radar altimeter, but only recently could it made over rough terrain using differential GPS (Parish et al 2007). With estimated OmniStar GPS altitude errors of 10 cm or less, and a typical air density of 0.3 kg m 23 , the potential error in the second term in (7) is only 0.3 Pa. We have confirmed this altitude accuracy during DEEPWAVE by comparing OmniStar with New Zealand ground GPS stations.…”
Section: B Correcting the Static Pressurementioning
confidence: 99%
“…As the autopilot is trying to maintain a constant pressure altitude, the variations in P C along a leg, especially for longer disturbances, come primarily from altitude (z) variations. This kind of correction has been made for several decades over water using a radar altimeter, but only recently could it made over rough terrain using differential GPS (Parish et al 2007). With estimated OmniStar GPS altitude errors of 10 cm or less, and a typical air density of 0.3 kg m 23 , the potential error in the second term in (7) is only 0.3 Pa. We have confirmed this altitude accuracy during DEEPWAVE by comparing OmniStar with New Zealand ground GPS stations.…”
Section: B Correcting the Static Pressurementioning
confidence: 99%
“…A coastal jet at the top of the marine boundary layer (MBL) is often embedded in this flow (e.g., Zemba and Friehe 1987;Burk and Thompson 1996;Rogers et al 1998;Parish 2000;Rahn and Parish 2007). This northerly wind regime is interrupted several times each summer by weak southerly flow adjacent to the coast that is often accompanied by fog or low stratus that moves northward along the coast.…”
Section: Introductionmentioning
confidence: 99%
“…LeMone and Tarleton (1986) and LeMone et al (1988) used altitude derived from accelerometer measurements instead of radar altitude in perturbation pressure studies around clouds suggesting that accuracies of 20 Pa can be obtained, but only with substantial empirical corrections and carefully flown legs. More recently, Parish et al (2007) and Parish and Leon (2012) demonstrated that Global Navigation Satellite System (GNSS, hereafter referred to as global positioning system -GPS) data can resolve both pressure gradients and perturbations associated with mesoscale and cloud-scale systems.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Differential global positioning system (dGPS) techniques use data from one or more stationary reference or base GPS stations which have precisely determined location to refine position estimates for the receiver on the aircraft. dGPS processing techniques using dual-frequency (L1/L2) carrier phase data can eliminate errors caused by ionospheric and tropospheric delays entirely, resulting in position estimates with accuracy of centimeters under optimal conditions (Parish et al, 2007).…”
Section: Measured Pressure Compared To Pressure Derived From Gps Altimentioning
confidence: 99%
See 1 more Smart Citation